Estimating taxable income responses with elasticity heterogeneity - Anil Kumar; Che-Yuan Liang (Uppsala University, Department of Economics, 2017)
We explore the implications of heterogeneity in the elasticity of taxable income (ETI) for tax-reform based estimation methods. We theoretically show that existing methods yield elasticities that are biased and lack policy relevance. We illustrate the empirical importance of our theoretical analysis using the NBER tax panel for 1979-1990. We show that elasticity heterogeneity is the main explanation for large differences between estimates in the previous literature. Our preferred, newly suggested method yields elasticity estimates of approximately 0.7 for taxable income and 0.2 for broad income.
urn:nbn:se:uu:diva-320178
Keywords: D11; H24; J22; 330; elasticity of taxable income; elasticity heterogeneity; tax reforms; panel data; preference heterogeneity